Alkaloids of Kopsia - Kam, Toh Seok; Lim, Kuan Hon (Elsevier, 2008)
This chapter presents a review on the chemistry and pharmacology of some recent Kopsia alkaloids and discusses the alkaloid structure type, in order of increasing complexity, and approximately along the lines of a progressing biosynthetic pathway. In each discussion, the aspects of structure elucidation, chemistry, synthesis, and biological activity of the alkaloids concerned explained. The occurrences of alkaloids in Kopsia species that have been chemically investigated are summarized in the chapter. The monoterpene alkaloids constitute a relatively small group of compounds and occur in several species, including K. pauciflora, K. profunda (K. macrophylla), and K. dasyrachis, from which several new monoterpene alkaloids related to skytanthine have been recently isolated. The North Borneo species K. pauciflora provided six such monoterpene alkaloids—namely, kinabalurines A–F. Kinabalurine G was isolated from the leaf extract of K. dasyrachis, another Kopsia from Malaysian Borneo. K. profunda (K. macrophylla) provided two more new monoterpene alkaloids, kopsilactone and kopsone, in addition to the known alkaloids 5,22-dioxokopsane, dregamine, akuammiline, tabernaemontanine, deacetylakuammiline, norpleiomutine, and kopsoffine. The leaves of K. dasyrachis also gave kopsirachine, which is constituted from union of the flavonoid, catechin, and two units of skytanthine. Nitaphylline was the only bisindole isolated from K. teoi, which otherwise yielded a large number of new indole alkaloids.